A comparative analysis of curvilinear configurations of the V-dipole antenna - Ayotunde A. Ayorinde; Sulaiman A. Adekola; Ike Mowete (Физика волновых процессов и радиотехнические системы)
Background. Curvilinear dipole antenna structures have been established as solution to the directivity problem associated with conventional dipole antennas, with length greater than half a wavelength. However, with the exception of the ‘concave Nu’ dipole, other curvilinear configurations of V-dipole antenna have yet to receive analytical attention in the open literature. This paper presents a comparative analysis of four of such configurations. Aim. Develop a detailed electric field integral equation formulation for internal electrodynamic problem of four curvilinear configurations of the V-dipole antenna structure, such that a method of moments solution becomes applicable. Methods. Unknown current distributions in the formulation are determined using the method of moments, with piece-wise linear basis and testing functions. Analytical results are then implemented in a FORTRAN computer program, for numerical results. Results. Analytical models for four curvilinear configurations of the V-dipole antenna as well as computational results for their input and radiation-zone characteristics. Conclusion. Computational results obtained reveal that in terms of maximum achievable directivity and return loss, the configuration with both arms curved, is the best performing; followed by the conventional-V, convex-Nu (one arm bent inwards), and concave-Nu (one arm bent outwards), in that order.